Comparison of volume-controlled and pressure-controlled ventilation on respiratory mechanics in laparoscopic bariatric surgery: randomized clinical trial - Ozyurt,Erhan (2019)
Abstract Background: It is not clear which mechanical ventilation mode should be used in bariatric surgery, one of the treatment options for patients with obesity. Objectives: To compare volume-controlled ventilation and pressure-controlled ventilation in terms of respiratory mechanics and arterial blood gas values in patients undergoing laparoscopic bariatric surgery. Methods: Sixty-two patients with morbid obesity scheduled for gastric bypass were included in this study. Their ideal body weights were calculated during preoperative visits, and patients were divided into two groups, volume-controlled ventilation and pressure-controlled ventilation. The patients were ventilated in accordance with a previously determined algorithm. Mechanical ventilation parameters and arterial blood gas analysis were recorded 5minutes after induction, 30minutes after pneumoperitoneum, and at the end of surgery. Also, the dynamic compliance, inspired O2 pressure/fractional O2 ratio, and alveolar-arterial oxygen gradient pressure were calculated. Results: Peak airway pressures were lower in patients ventilated in pressure-controlled ventilation mode at the end of surgery (p = 0.011). Otherwise, there was no difference between groups in terms of intraoperative respiratory parameters and arterial blood gas analyses. Conclusions: Pressure-controlled ventilation mode is not superior to volume-controlled ventilation mode in patients with laparoscopic bariatric surgery.